Code Generator Python dari Bentuk XML Metadata Interchange (XMI) pada Unified Modeling Language (UML) 2.0 - I Made Murwantara; Pujianto Yugopuspito; Johan Julianto Roestam (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
Unified Modeling Language (UML) code generator tools are available to parsing UML diagrams intosource code. Currently, UML 2.0 tools that can parse into Python’s source code are still in work planningphase. This research aims to create UML code generator that can parse XML Metadata Interchange (XMI) intoPython’s source code. XMI defines the design of program using UML 2.0 standard. Design process of thisprototype uses UML standard version 2.0. On this research, algorithm for rules of parsing XMI into Python’ssource code was created.Keywords: UML, Python, Parsing